Mykola Lebovka's 60th birthday (Condensed Matter Physics, 2014)
May 15 this year was the 60th birthday of Mykola Lebovka, an outstanding Ukrainian scientist in the field of physical chemistry of condensed matter, Doctor Habilitus in Physics and Mathematics, professor, head of the Department of Physical Chemistry of Disperse Minerals at F.D. Ovcharenko Institute of Biocolloidal Chemistry, National Acad.Sci. of Ukraine.